Early matrix metalloproteinase-12 inhibition worsens post-myocardial infarction cardiac dysfunction by delaying inflammation resolution. (15th April 2015) - Iyer, Rugmani Padmanabhan; Patterson, Nicolle L.; Zouein, Fouad A.; Ma, Yonggang; Dive, Vincent; de Castro Brás, Lisandra E.; Lindsey, Merry L.
Abstract: Rationale: Matrix metalloproteinases (MMPs) regulate remodeling of the left ventricle (LV) post-myocardial infarction (MI). MMP-12 has potent macrophage-dependent remodeling properties in the atherosclerotic plaque; however, post-MI roles have not been examined. Objective: The goal was to determine MMP-12 post-MI mechanisms. Methods and results: Male C57BL/6J mice (3–6 months old) were subjected to left coronary artery ligation. Saline or the RXP 470.1 MMP-12 inhibitor (MMP-12i; 0.5 mg/kg/day) was delivered by osmotic mini-pump beginning 3 h post-MI, and mice were sacrificed at day (d)1, 3, 5 or 7 post-MI and compared to d0 controls (mice without MI; n = 6–12/group/time). MMP-12 expression increased early post-MI, and contrary to expected, neutrophils were a surprising early cellular source for MMP-12. MMP-12i reduced MMP-12 activity 33 ± 1% at d1 post-MI. Despite similar infarct areas and survival rates, MMP-12i led to greater LV dilation and worsened LV function. At d7 post-MI, MMP-12i prolonged pro-inflammatory cytokine upregulation ( IL1r1, IL6ra, IL11, and Cxcr5 ) and decreased CD44 (both gene and protein levels). Hyaluronan (HA), a CD44 ligand, was elevated at d1 and d7 post-MI with MMP12i, as a result of decreased fragmentation. Because CD44-HA regulates neutrophil removal, apoptosis markers were evaluated. Caspase 3 increased, while cleaved caspase 3 levels decreased in MMP-12i group at d7 post-MI, indicating reduced neutrophil apoptosis. In isolated neutrophils, active MMP-12 directly stimulated CD44, caspase 3, and caspase 8 expression. Conclusion: Our results reveal a novel protective mechanism for MMP-12 in neutrophil biology. Post-MI, MMP-12i impaired CD44–HA interactions to suppress neutrophil apoptosis and prolong inflammation, which worsened LV function. Highlights: MMP-12 expression increased early post-MI, and the neutrophils are a previously unknown early source. MMP-12 inhibition worsened LV dysfunction, and increased ECM degradation and pro-inflammatory cytokine levels at d7 post-MI MMP-12 inhibition disrupted CD44–HA interaction and reduced neutrophil apoptosis to impair resolution of inflammation. Our results reveal a unique and protective role of MMP-12 in the early post-MI left ventricle.